Investigation of the metal/porcelain interface in LASER-welded Ni-Cr-Mo alloy - Ernesto, Vívian Aparecida Ricardo Teixeira [UNESP]; Guastaldi, Antonio Carlos [UNESP] (My University, 2009)
The interface formed between the metal and the porcelain of laser-welded Ni-Cr-Mo alloy was studied on a metallurgical basis. The characterization was carried out by using optical microscope, electron scan microscopy and X-ray dispersive spectroscopy techniques and mechanical three-point flexion tests, in the laser-welded region, with and without porcelain. The union of the porcelain with the alloy is possible only after the oxidation of the metallic surface and the subsequent application of a bonding agent known as opaque. The porcelain applied to the base metal and weld bead showed different behaviours - after the flexion test, the base metal showed cracks, while that in the weld bead broke away completely. It was noted that the region subjected to laser welding had lower adherence to the porcelain than the base metal region, due to microstructural refinement of the weld bead. These results can be shown by the X-ray dispersive spectroscopy carried out on the regions studied. The flexion tests demonstrated that the Ni-Cr-Mo alloy subject to laser welding had significant alterations in its mechanical properties after application of the porcelain.
Keywords: Laser beam welding; Metallo-ceramic; Ni-Cr-Mo alloy; Prostheses; Base metals; Bonding agent; Laser welding; Metallic surface; Microstructural refinement; Optical microscopes; Weld bead; Alloys; Cerium alloys; Chromium; Industrial applications; Laser beams; Laser welding machines; Lasers; Mechanical properties; Metals; Molybdenum; Nickel; Optical microscopy; Porcelain; Prosthetics; Welds; Molybdenum alloys